PENDAMPINGAN REVITALISASI TANAMAN OBAT KELUARGA (TOGA) GUNA MENINGKATKAN KESEHATAN DAN EKONOMI KELUARGA MANDIRI DI DESA KALISAMPURNO, KECAMATAN TANGGULANGIN, KABUPATEN SIDOARJO - Kirom, Askhabul; Marinten Mawarti; Nurul Ilmiyah; Nur Rochmat Ali; M. Lailul Karim (JURNAL PENGABDIAN PAPUA, 2024)
Socialization Lack of knowledge about the use of medicinal plants, as well as the TOGA conservation movement, which is one of the advantages of this village, has received little attention from the community to restore the function and purpose of the village's TOGA garden and maintain its sustainability. This assistance aims to revitalize Family Medicinal Plants (TOGA) in order to improve the health and economy of independent families. This assistance was carried out in Kalisampurno Village, Tanggulangin District, Sidoarjo Regency. This assistance uses the ABCD (Asset Based Communities Driven Development) method through the stages of the 5-D cycle; Define, Discovery, Dream, Design, and Deliver or Destiny. The results of assistance in the revitalization of family medicinal plants (Toga) through planting TOGA plants according to their type, developing fertilizer formulas that are more effective and environmentally friendly, planting and equipping TOGA plants, installing TOGA plant names and inaugurating the TOGA garden gate in Kalisampurno Village. Keywords: Revitalization; TOGA; Health; Economy